2020
DOI: 10.3390/cancers12061610
|View full text |Cite
|
Sign up to set email alerts
|

The Antihistamine Deptropine Induces Hepatoma Cell Death through Blocking Autophagosome-Lysosome Fusion

Abstract: Some antihistamines have exhibited significant antitumor activity alone or in combination with other therapies in in vitro and clinical studies. However, the underlying mechanisms of how antihistamines inhibit hepatocellular carcinoma proliferation are still unknown. We first screened the antiproliferation activity of 12 benzocycloheptene structural-analogue drugs, and results showed that deptropine was the most potent inhibitor of both Hep3B and HepG2 human hepatoma cells. Deptropine significantly increased l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…51 In our previous cell model experiments, we observed that the administration of deptropine could inhibit the combination of autophagosome and lysosome and, ultimately, induce hepatoma cell death. 39 Although no mechanism have been discussed in the aforementioned studies, AH is nevertheless believed to have a role in immunoregulation. Moreover, unlike other anti-inflammatory drugs, AH can induce hepatoma cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 In our previous cell model experiments, we observed that the administration of deptropine could inhibit the combination of autophagosome and lysosome and, ultimately, induce hepatoma cell death. 39 Although no mechanism have been discussed in the aforementioned studies, AH is nevertheless believed to have a role in immunoregulation. Moreover, unlike other anti-inflammatory drugs, AH can induce hepatoma cell death.…”
Section: Discussionmentioning
confidence: 99%
“…38 Our previous study demonstrated that deptropine (an AH) blocks the fusion of autophagosome and lysosome and, consequently, induced hepatoma cell death. 39 Zhao et al 40 revealed upregulation of histamine receptors promote tumor progression in HCC and He et al 41 found the possible antiviral effects of AHs in HCV. Despite the extensive application of targeted therapy, current treatments for advanced HCC remain unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Cyproheptadine has cytotoxic effects and increased annexin V staining for cell death, which raise the levels of poly ADP-ribose polymerase (PARP) and its cleaved form, inducing apoptosis in HCC cell lines ( 3 , 7 , 11 ). In addition, cyproheptadine can suppress the PI3K/AKT signaling pathway in carcinoma cells and multiple myeloma cells, leading to cell cycle arrest in the G1 phase and G1/S transition, resulting in apoptosis and necrosis ( 7 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…130 In a recently concluded study, 13 induced hepatoma cell death by blocking autophagosome−lysososome fusion, that is, it initiated autophagy, but failed to complete its maturation. 131 In addition, 13 moderately activated caspase-3, -8, and -9 and partially contributed to the cell death via apoptosis activation. Furthermore, Hep3B tumor xenograft studies in athymic mice showed a significant reduction in the tumor volume, thereby supporting the in vitro observations.…”
Section: ■ Drug Repurposing For Csc Targetingmentioning
confidence: 98%
“…It is an inhibitor of ALDH with potent activity against breast CSCs . In a recently concluded study, 13 induced hepatoma cell death by blocking autophagosome–lysososome fusion, that is, it initiated autophagy, but failed to complete its maturation . In addition, 13 moderately activated caspase-3, -8, and -9 and partially contributed to the cell death via apoptosis activation.…”
Section: Synthetic Organic Molecules/nces As Anti-csc Agentsmentioning
confidence: 99%